INTRODUCTION OF AN INDIVIDUAL EDUCATIONAL TRAJECTORY IN A HIGHER EDUCATION INSTITUTION THROUGH THE IMPLEMENTATION OF A CATALOG OF ELECTIVE DISCIPLINES - Buinytska, Oksana; Varchenko-Trotsenko, Liliia; Smirnova, Valeriia; Tiutiunnyk, Anastasiia; Hrytseliak, Bohdan; Matasar, Yevhen (Journal of Information Technologies in Education (ITE), 2024)
Institutions of higher education are increasingly faced with the diversity of needs and expectations of students, which calls into question traditional educational curricula. In this context, there is a need to introduce new approaches that provide students with greater flexibility in learning and the opportunity to independently shape their educational path. One of these approaches is an individual educational trajectory, which allows students to actively participate in the formation of their individual learning paths, increasing their motivation and interest in the learning process. The urgency of introducing an individual educational trajectory in universities reflects the need to adapt the educational system to modern realities and individual needs of students. It is also a response to the challenge of ensuring flexibility, differentiation and personalization of training, which is becoming increasingly important in light of the rapidly changing labor market and the requirements for the competencies of future professionals. The article examines the possibility of introducing an individual educational trajectory for students of higher education institutions through the implementation of the “catalog of elective disciplines” module in the e-learning system, evaluation and planning of the educational process, determination of success criteria and support of students in the process of selection and advancement along an individual trajectory. The relevance of this issue is due to changes in the modern educational environment, which requires a more flexible approach to learning to take into account the individual needs and interests of students. An analysis of research related to the implementation of an individual educational trajectory and the implementation of the catalog of selective disciplines was carried out.